Mineralization of the Textile Dye Acid Yellow 42 by Solar Photoelectro-Fenton in a Lab-Pilot Plant - Romero-Figueroa, J (Elsevier B.V., 2016)
A complete mineralization of a textile dye widely used in the Chilean textile industry, acid yellow 42 (AY42), was studied. Degradation was carried out in an aqueous solution containing 100 mg L−1 of total organic carbon (TOC) of dye using the advanced solar photoelectro-Fenton (SPEF) process in a lab-scale pilot plant consisting of a filter press cell, which contains a boron doped diamond electrode and an air diffusion cathode (BDD/air-diffusion cell), coupled with a solar photoreactor for treat 8 L of wastewater during 270 min of electrolysis. The main results obtained during the degradation of the textile dye were that a complete transformation to CO2 depends directly on the applied current density, the concentration of Fe2+ used as catalyst, and the solar radiation intensity. The elimination of AY42 and its organic intermediates was due to hydroxyl radicals formed at the anode surface from water oxidation and in the bulk from Fenton s reaction between electrogenerated H2O2 and added Fe2+. The application of solar radiation in the process (SPEF) yield higher current efficiencies and lower energy consumptions than electro-Fenton (EF) and electro-oxidation with electrogenerated H2O2 (E O[sbnd]H2O2) by the additional production of hydroxyl radicals from the photolysis of Fe(III) hydrated species and the photodecomposition of Fe(III) complexes with organic intermediates. Moreover, some products and intermediates formed during mineralization of dye, such as inorganic ions, carboxylic acids and aromatic compounds were determined by photometric and chromatographic methods. An oxidation pathway is proposed for the complete conversion to CO2. © 2016 Elsevier B.V.